Reciclagem de óleo de cozinha: análise de redes de coleta enfatizando experiências paulistas - Oliveira, Rosicler Barbosa de (2014)
The used cooking oil is a waste that can be recycled resulting in significant environmental benefits. These benefits are aligned to the three elements of the triple bottom line, namely: environmental - preservation of natural resources; social - employment and income generation; and economic - reuse of oil waste for several purposes. The aim of this study is to analyze how networks for recycling cooking oil waste are formed, both in Brazil and abroad. Some institutions are disseminating this idea and linking various actors (as nodes) to their local recycling networks, including: suppliers of used oil (final consumers); collection points; processors (companies that collect, filter, and sell the waste); and companies that use it as a raw material for manufacturing a number of products. The analysis focused mainly on two organizations: Instituto Triângulo and Ecóleo, in order to understand the process of collecting waste cooking oil in Brazil and what are prospects for expansion. The research methodology was based on both bibliographic and document review, with semi-structured and open end questionnaires were used in these interviews to assess factors that stood out as the most important for partners and suppliers to join the Instituto Triângulo s network. Researches showed that keeping actors by Instituto Triângulo depends on a number of situations, as follows: (i) best market opportunity offers provided by exchanges for cleaners or soap or even cash payment for the oil waste; (ii) concerns about regulations (that is, if partners are working under the law); (iii) disrespect to previous agreements on collection schedule etc. It was found that Ecóleo works as an association of 25 companies. The information disclosure on the work performed by these associated companies is done via advertising materials such as flyers and posters, and lectures to awareness the society about the correct dispose of used vegetable oil. It was also realized that the Ecóleo s network as an association has helped this NGO to expand its activities to a number of states in Brazil other than São Paulo. The result of this study shows that network promotes dissemination of information, amplifying its reach, and facilitate access to actors who are the network edge (final consumer), and the information can be multiplied for them.